2022
DOI: 10.1002/path.6018
|View full text |Cite
|
Sign up to set email alerts
|

Role of MIF1/MIF2/CD74 interactions in bladder cancer

Abstract: Macrophage migration inhibitory factor (MIF1) is a pleiotropic cytokine involved in inflammation and cancer. Genetic knockout of Mif1 in the validated N‐butyl‐N‐(4‐hydroxybutyl) nitrosamine (BBN) model of bladder cancer (BCa) resulted in stage arrest at non‐muscle‐invasive disease in prior studies. Small‐molecule inhibition of MIF1 reduced cancer‐associated outcomes, but it did not fully recapitulate genetic models. D‐dopachrome tautomerase (gene symbol DDT), commonly referred to as MIF2, is a functional homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…It has also been proposed to be predictive of both metastasis and clinical outcomes in various cancers 14 , 21 . Inhibition of MIF1/MIF2 reduces the tumor burden of bladder cancer in preclinical models, an effect that was found to be accomplished in part through activation of CD74, suggesting the significance of CD74 in tumor development 22 . However, there is minimal information on its function in other cancers.…”
Section: Discussionmentioning
confidence: 95%
“…It has also been proposed to be predictive of both metastasis and clinical outcomes in various cancers 14 , 21 . Inhibition of MIF1/MIF2 reduces the tumor burden of bladder cancer in preclinical models, an effect that was found to be accomplished in part through activation of CD74, suggesting the significance of CD74 in tumor development 22 . However, there is minimal information on its function in other cancers.…”
Section: Discussionmentioning
confidence: 95%
“…In cancer, MIF/CD74 axis is considered to be a signaling pathway that pro-tumor. Benjamin et al found that MIF expression is increased in bladder cancer patients, and the use of the MIF inhibitor 4-IPP can suppress tumor growth [ 70 ]. Israel et al discovered that MIF is highly expressed in Luminal B, HER2, and Basal subtypes of breast cancer, but its expression is not prognostically relevant in any subtype of breast cancer [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…MIF-KO murine bladder cancer models demonstrated decreased vascularization and tumor stage [91]. 4-IPP treatment in murine bladder cancer models resulted in decreased tumor weights in MIF-KO versus WT mice, suggesting an additive contribution of DDT inhibition [198]. In bladder cancer cells, MIF knockdown produced a dose-dependent reduction in growth [203].…”
Section: Central Nervous System Cancersmentioning
confidence: 93%
“…Urogenital Cancers 4.8.1. Bladder Cancer MIF and DDT overexpression has been observed in TCGA analysis of bladder cancers [198,199]. Similarly, CD74 overexpression is detected in high-grade invasive bladder cancer and is associated with proliferation, invasion, and angiogenesis of HT-1376 bladder cancer cells [200][201][202].…”
Section: Central Nervous System Cancersmentioning
confidence: 99%